Tracking retention and transport of ultrafine polystyrene in an asthmatic mouse model using positron emission tomography. (1st September 2013) - Enright, Heather A.; Bratt, Jennifer M.; Bluhm, Andrew P.; Kenyon, Nicholas J.; Louie, Angelique Y.
ABSTRACT: Upon exposure to particulates, asthmatic individuals are more susceptible to deleterious health effects and increased morbidity and mortality when compared to healthy individuals. These effects are not limited to the respiratory system; increases in acute cardiovascular events have been observed. The development of extrapulmonary illnesses has led to interest in determining whether particles move out of the lungs and whether transport of particles differs for asthmatic individuals. Differences in particle deposition and retention in asthmatic versus normal subjects have been explored in the literature using the gamma camera, a two-dimensional imaging technique. Herein we report the deposition and fate of 64 Cu-labeled 100 nm polystyrene particles in a mouse model of asthma using positron emission tomography (PET). All animals were handled humanely under an approved protocol (UC Davis Institutional Animal Care and Use Committee). Particles were administered by intratracheal instillation and animals were imaged over 48 hours using PET. Biodistribution was determined from images using Regions of Interest (ROI) analysis. After 48 hours, for the asthmatic animals, we observed that ∼28% of the initial dose is cleared from the lungs; particle accumulation in small amounts is evident in the GI (gastrointestinal) tract, liver, and bladder. This decrease in lung retention is significantly different when compared to the normal mouse (∼11%DD), which showed minimal particle transport out of the lung ( P < 0.001). This study indicates that ultrafine particles (UFP) undergo enhanced transport out of the lungs in an asthma model. This observed transport may facilitate the adverse peripheral effects associated with particulate exposure.